2016
DOI: 10.1590/1678-457x.0084
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antioxidant activity of the pulp of Jatobá-do-cerrado

Abstract: Dxygen metabolism in cells causes the production of free radicals, which produce damage, including changes in cell structure and function. Antioxidants are substances that, at low concentrations, slow down or prevent oxidation. Fruits and vegetables contribute to the dietary supply of these compounds. The flora of the Cerrado in Brazil has shown to have high levels of bioactive compounds. This study aimed to characterize the antioxidant activity of the pulp of jatobá-do-cerrado in vitro and in vivo. In vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The antioxidant activity of the extracts was strongly dependent on the extraction solvent (Arakaki et al, 2016). The choice of extraction solvent is a crucial step for the assessment of antioxidant activity of extracts, since polarity of solvents determines the recovery of natural antioxidants from herbals (Goulas et al, 2012;Galanakis et al, 2013).…”
Section: Effect Of Extracting Solvent On the Antioxidant Activitiesmentioning
confidence: 99%
“…The antioxidant activity of the extracts was strongly dependent on the extraction solvent (Arakaki et al, 2016). The choice of extraction solvent is a crucial step for the assessment of antioxidant activity of extracts, since polarity of solvents determines the recovery of natural antioxidants from herbals (Goulas et al, 2012;Galanakis et al, 2013).…”
Section: Effect Of Extracting Solvent On the Antioxidant Activitiesmentioning
confidence: 99%
“…The fibrous residue of jatobá-da-mata flour had a high polyphenol concentration, which is close to jatobá-do-cerrado flour content (786 mg GAE/100 g) 9 . Jatobá-da-mata flour is a good source of polyphenols, having a concentration which is close to that reported for hydrocetonic extract of jatobádo-cerrado flour, of 536 mg GAE/100 g 2 , and higher than that of baru pulp flour (292 mg GAE/100 g) 21 .…”
Section: Discussionmentioning
confidence: 51%
“…The antioxidant potential of the pulp of jatobá-do-cerrado (Hymenaea stigonocarpa Mart.) was investigated by Arakaki et al 9 , who reported high phenolic acid and tannin content, and antioxidant activity estimated by DPPH assay. However, jatobá-damata (Hymenaea courbaril, var.…”
Section: Introductionmentioning
confidence: 99%
“…The yield of methanol extraction increases alongside the solubility of antimicrobial plant components increases (Merveill et al 2017). Several workers have reported that a wide range of significant differences for the yields could be due to various factors such as time of extraction, type and part of plant materials used, extraction of solvent polarities, fineness of powder and extent of dryness (Maharjan et al 2010;Ngeny 2012;Silva et al 2014;Naima et al 2015;Arakaki et al 2016;Felhi et al 2017).…”
Section: Weight Of Plant Materialsmentioning
confidence: 99%
“…The previous studies indicated that medicinal plants have different antimicrobial activities depending on extraction solvent, plant types and amount of the presence of bioactive compound (Sequeira et al 2013;Stankovi et al 2015;Bahraminejad et al 2015;Arakaki et al 2016). These plants have huge availability nearly our village and easy preparation method can be used by farmers.…”
Section: Weight Of Plant Materialsmentioning
confidence: 99%